The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ijgo.14029
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal hysterectomy and high frailty score are associated with complications among older patients

Abstract: As the US population of older adults increases, the number of older hysterectomy patients will increase. 1 Evidence demonstrates a wide range of postoperative outcomes in older adults of the same chronologic age. Consequently, frailty has been examined as a way to better predict which older patients have higher risk for poor surgical outcomes. 2 Frailty has been conceptualized as an "age-related, multidimensional state of decreased physiologic reserves that results in diminished resiliency, loss of adaptive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Indeed, numerous studies demonstrated the advantages of MIS (either vaginal or laparoscopic surgery) over open surgery, indicating benefits such as lower perioperative morbidity and faster recovery [6]. In particular, as reported by a recently published study which included data of patients of the American College of Surgeons' National Surgical Quality Improvement Program database aged 60 years or older who underwent total hysterectomy for benign indication, the risk of surgical complications related to open surgery is even higher in case of frail patients [13]. Some nationwide population-based cohort studies showed a steady decrease in AH in the last decades.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous studies demonstrated the advantages of MIS (either vaginal or laparoscopic surgery) over open surgery, indicating benefits such as lower perioperative morbidity and faster recovery [6]. In particular, as reported by a recently published study which included data of patients of the American College of Surgeons' National Surgical Quality Improvement Program database aged 60 years or older who underwent total hysterectomy for benign indication, the risk of surgical complications related to open surgery is even higher in case of frail patients [13]. Some nationwide population-based cohort studies showed a steady decrease in AH in the last decades.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible this is due to the higher percentage of abdominal hysterectomies and concomitant procedures within the oncology cohort; in the Wainger et al) study looking at the effect of frailty on postoperative complications by type of hysterectomy, abdominal hysterectomy was associated with a higher risk of complication in frail patients. ( Wainger et al, 2021 ) This speaks to a significant challenge when studying frailty’s association with surgical complications—specifically, the difficulty separating the degree to which complications are due to a patient’s frailty status versus inherent risks of the surgery itself. However, to try and account for this, we adjusted for route of hysterectomy and performance of concomitant procedures in our final model, with the above result.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, mFI-5 appears to have been the least predictive of outcomes in the ovarian cancer subgroup, which was somewhat surprising given that the two other studies looking at frailty in gynecologic surgery (which both included ovarian cancer patients, although did not examine these patients as a subgroup) found an association between frailty and complication risk. ( Wainger et al, 2021 , Mah et al, 2022 ) We hypothesize this may be a result of our inability to distinguish stage and those undergoing hysterectomy as part of a primary debulking versus interval debulking following neoadjuvant chemotherapy. This distinction is potentially significant, given that those undergoing a primary debulking may be having a more aggressive procedure with inherently increased risk of death and complications, and stage is independently predictive of postoperative complications per the findings in Mah et al ( Mah et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%